Somebody's darling : essays on the Civil War - Gramm, Kent (Indiana University Press, 2002)
In his latest book, Kent Gramm examines the meaning of the Civil War experience in our lives and explores philosophical and personal aspects of the War that lie outside the scope of traditional historical study. He probes the meaning of Gettysburg, the Wilderness, and Antietam; the lives of U.S. Grant, Robert E. Lee, O.O. Howard, and Chief Joseph of the Nez Perce; and the legacy of the unknown participant, "somebody's darling," for whom the war would come to encompass all things. The Iron Brigade appear.